A Functional Game Application for Korean Words Learning Based on Smartphone Environments - Choi, YoungMee (Journal of Multimedia Information System, 2019)
In this paper, the prototyping process for developing syllable-initial consonant-based game ‘Korean Guards’ is described. Users may effectively learn Korean words using alphabetically sequential approaches, but the easiness of access bestowed on the smart environments and game algorithms could be fully utilized for the functional advantages for educational purposes. This functional game is developed on Android OS and the prototypical outcome is shown. KCI Citation Count: 0